Sathāban Wičhai Phāsā læ Watthanatham ph̄ưa Phatthanā Chonnabot, Mahāwitthayālai Mahidon (Sathāban Wičhai Phāsā læ Watthanatham ph̄ưa Phatthanā Chonnabot, Mahāwitthayālai, 2000)
Courses offered at the Institute of Language and Culture for Rural Development, Mahidol University.